Ecological patterns of Chironomidae assemblages in Dynaric karst springs - Płóciennik M.; Dmitrović D.; Pešić V.; Gadawski P. (Knowledge and Management of Aquatic Ecosystems, 2016)
Springs are one of important freshwater habitats in the Dynaric Mountains. Nevertheless, there were no intensive studies on dipteran communities in the region. Here we present an ecological analysis of Chironomidae communities recorded from a set of 27 springs along the Cvrcka River mainstream (the Republic of Srpska, Bosnia and Herzegovina). Environmental classification of Cvrcka springs divide them into three groups reflecting the level of human impact. Chironomidae communities divide investigated springs into three groups more dependent on bottom substrate quality. CCA indicates that the hard bottom and altitude are primary (significant) factors determining midge assemblages. Secondary factors influencing communities are oxygen concentration and conductivity. There are clear differences in diversity and abundance in these three types of spring communities. Type II aggregates natural sites for Cvrcka valley. Samples characterized by high abundance of Chironomus seems to be an outliers in Cvrcka canyon. Eucrenon and hypocrenon communities are distinct, but no differences in the diversity level or the environmental assemblage relation were recorded for both mesohabitats. This study proves that solely environmental classification of spring habitats reflects well human impact, but invertebrate communities may not clearly follow general classification, reacting to a set of natural and altered conditions.